Preparation of goat milk powder with Lactobacillus casei L61 and antioxidant peptides: optimization of the composite thermal protectants and evaluation of storage stability. Issue 14 (1st October 2020) - Shu, Guowei; Zheng, Qiqi; Chen, Li; Kou, Jianbo; Guo, Yuliang; Zhang, Meng
Abstract: The Lactobacillus casei L61 has great ability for producing antioxidant peptides. For reducing the mortality of L. casei L61 in spray drying process, the Box-Behnken design (BBD) was adopted to optimize the composite thermal protective agent formula. The results exhibited that the composite thermal protective agent formula of L. casei L61 contained glucose at 6.03% (w/v), skim milk at 18.98 g/L, and glycerol at 12.50 mL/L. Under the optimal conditions, the average survival of L. casei L61 in the fermented goat milk reached 14.58 ± 0.72% after heat treatment at 75 °C for 10 min, which was higher than the control (13.14%). The average hydroxyl free radical scavenging activity of L. casei L61 reached 85.09 ± 0.98%, which was not significantly different from the predicted value (86.83%). Therefore, the BBD is feasible for optimizing the composite thermal protective agent formula of L. casei L61. Under the optimal conditions with the inlet air temperature of 130 °C and feed rate of 4.5 mL/min, the maximum viable counts and survival rate of L. casei L61 were 7.46 × 10 8 cfu/g and 23.41 ± 1.28%, respectively. More importantly, the storage stability of antioxidative probiotic goat milk powder was predicted by temperature acceleration test. The shelf life of antioxidative probiotic goat milk powder was estimated to be 352 days at 4 °C and 117 days at 25 °C, embodying the great long-term stability. This study provides a technical reference for industrialized production of probiotic goat milk powder.